Analisis Terjadinya Arus Netral Pada Trafo Distribusi 160 kVA - Arfita Yuana Dewi; Asnal Effendi; Fahody M Syafar (Universitas Batanghari Jambi, 2021)
The Power distribution in a 3-phase system, cannot be separated from the flow of current in the neutral of the transformer, which will cause power losses (losses) where current flows into the neutral conductor and losses that flow into the neutral conductor. This study was conducted to determine the causes and magnitude of power losses that occur due to the occurrence of neutral current flowing in the neutral conductor in a 160kVA distribution transformer. The research location taken is the Distribution Transformer (G187 T) which is located on Jl. Hos Cokroaminoto Wisma Ombilin where load imbalances often occur. From the results, it can be seen that if the neutral wire has a cross-sectional size of 50 mm2, the current that passes through the neutral wire is 6.4% for the day and for the cross-sectional size of the wire is 70 mm2, it can reduce the power flowing to the neutral by a percentage of 4.77%. for the daytime. Efficiency value that occurs is greater at night that is 94.87% while for the day it is 93.44%. For the distribution of each - each phase, especially the S phase, so that it can be balanced because the power supplied to the S phase is too small. We recommend that the current flowing in the neutral wire must be channeled to the ground so that the current flowing in the neutral wire becomes zero.